The relationship between (stigmatizing) views and lay public preferences regarding tuberculosis treatment in the Eastern Cape, South Africa - Nieboer Anna P; Cramm Jane M (BMC, 2011)
Abstract Background Tuberculosis (TB) and human immune virus/acquired immune deficiency syndrome (HIV/AIDS) stigmas affect public attitudes toward TB treatment and policy. This study examined 'stigmatizing' ideas and the view that 'TB patients should line-up in the chronic illness queue' in relation to preferences and attitudes toward TB treatment. Methods Data were gathered through a survey administered to respondents from 1,020 households in Grahamstown. The survey measured stigmatization surrounding TB and HIV/AIDS, and determined perceptions of respondents whether TB patients should queue with other chronically ill patients. Respondents selected support and treatment options they felt would benefit TB patients. Statistical analysis identified the prevalence of TB and HIV/AIDS stigmas. Logistic regression analyses explored associations between stigmatizing ideas, views regarding TB patients in the chronic illness queue, and attitudes toward support and treatment. Results Respondents with TB stigmatizing ideas held positive attitudes toward volunteer support, special TB queues, and treatment at clinics; they held negative attitudes toward temporary disability grants, provision of information at work or school, and treatment at the TB hospital. Respondents who felt it beneficial for TB patients to queue with other chronically ill patients conversely held positive attitudes toward provision of porridge and disability grants, and treatment at the TB hospital; they held negative attitudes toward volunteer support, special TB queues, information provision at work or school, and treatment at clinics. Conclusion These results showed that two varying views related to visibility factors that expose patients to stigmatization (one characterized by TB stigma, the other by the view that TB patients should queue with other chronically ill patients) are associated with opposing attitudes and preferences towards TB treatment. These opposing attitudes complicate treatment outcomes, and suggest that complex behaviors must be taken into account when designing health policy.